The Study Of Kaṭha Upaniṣad Text And Its Implementation At Sai Study Group Denpasar - I Made Adi Wirawan; I Ketut Sumadi; I Gede Suwindia (Jayapangus Press, 2019)
This research focuses on the study of the Kaṭha Upaniṣad text and its implementation in social life. The Kaṭha Upaniṣad is one of the important books among the other Upanishad books. This book also contains many teachings of Hindu theology and divine philosophy. Ātman and Brahman are important discussions in the Kaṭha Upaniṣad. The philosophical side of the Kaṭha Upaniṣad is closely related to human concepts and the way of life to be free from suffering. The Kaṭha Upaniṣad offers a unique perspective by understanding the main character of mankind, namely Ātman (God within oneself). The most tangible context of the Kaṭha Upaniṣad teachings can be seen in the Sai Study Group (SSG) Denpasar. Sai Baba’s discourses do not indeed refer to the Kaṭha Upaniṣad as the main reference, but every activity at the Sai Study Group Denpasar has an alignment with the Vedic teachings.